(untitled) (Al-Farooq Journal of Sciences, 2026)
The research aims to identify the economic effects of the fuel subsidy lifting policy in Libya during the period (2006-2023). The study used the descriptive analytical approach and concluded that there is no statistically significant effect of lifting fuel subsidies in Libya on both the GDP growth rate and the inflation rate and unemployment rate. The study recommended the need to conduct more studies and research through which the economic effects of the fuel subsidy lifting policy can be studied and work to increase the ability of the Libyan authorities to confront fuel smuggling and the need to develop mechanisms through which support can be converted from in-kind to cash and ensure that it reaches those entitled to it.